Novel one-pot multi-component synthesis of 3,3 `-disubstituted oxindole and spirooxindole scaffolds via Sn-catalyzed C(sp(3))-H functionalization of azaarenes by sequential Knoevenagel-Michael-cyclization reaction - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek Abdul Rashid (RSC Advances, 2015)
Sn-catalyzed C(sp(3))-H bond functionalization of 2-methyl azaarenes/2-(azaaryl)methanes has been achieved for the first time in a one-pot multi-component reaction with isatin and active methylene compounds via tandem sequential Knoevenagel-Michael-intramolecular C-N cyclization. This strategy provides new cost-effective access to potent and biologically/medicinally important spirooxindoles/3,3'-disubstituted 2-oxindoles in good to excellent yields.